IMPLEMENTASIAN STANDAR NASIONAL PERPUSTAKAAN SMP/MADRASAH TSANAWIYAH DI SMPN 01 KOTA BENGKULU - Aqiqah Bulan Sari; Anggun Vedia; Rahmat Alifin Valentino; Igirisa, Miftahunnsa; Piona Chintia Bella; Dea Ramadhani; Jesi Ramadhani (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2024)
School libraries play an important role in supporting the learning process and improving literacy in students. Although Law No. 20 of 2003 concerning the national education system emphasizes the importance of providing learning resources, many school libraries still face obstacles in meeting these standards, one of which is the SMPN 01 Bengkulu City Library. This study aims to investigate the implementation of national library standards at SMPN 01 Bengkulu City and provide an overview of the condition of the library and provide recommendations for improving its quality. The research method used is a qualitative method, through interviews, observations, documentation, and literature studies. The results of the study indicate that although the SMPN 1 Bengkulu City library has sufficient collections, its management is still not optimal, especially in compiling, organizing, and adjusting to the applicable curriculum. Although the library facilities and infrastructure are quite adequate, there are problems such as the location of the library is not strategic and there are no mandatory programs and information literacy. As well as the need for library experts. The proposed solutions include improving the location of the library, developing these programs, and finding other solutions to meet the need for library staff. In terms of library management, the existence of librarians is very important, and the need for additional library staff with special skills is also recognized. The SMPN 1 school library is also advised to have a Library Identification Number (NPP) to identify and record the library. With improvements and innovations, it is hoped that the SMPN 1 library in Bengkulu city can improve the quality of services based on the Regulation of the Head of the National Library of the Republic of Indonesia Number 11 of 2017 concerning National Standards for Junior High Schools/Tsanawiyah Madrasahs